2020
DOI: 10.1108/wje-06-2020-0215
|View full text |Cite
|
Sign up to set email alerts
|

Double-diffusive free convective flow of Casson fluid due to a moving vertical plate with non-linear thermal radiation

Abstract: Purpose This paper aims to report the investigation of over heat and mass transfer of convective Casson fluid flow over a moving vertical plate with nonlinear thermal radiation and convective boundary conditions. Design/methodology/approach The main partial differential equations of the flow, heat and concentration profiles were rehabilitated to nonlinear ordinary differential equations by using an appropriate similarity transformation. The resultant nonlinear ordinary differential equations (ODEs) are solve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Shehzad et al 7 analyzed the Casson liquid stream with radiation effect. The impact of chemical reaction on the stream of Casson liquid through a stretching surface was addressed by Khan et al 8 Nandeppanavar et al 9 scrutinized the radiation effect on convective stream of a Casson liquid instigated by a moving upright plate. Alkasasbeh et al 10 scrutinized the blood‐based Casson nanofluid stream over an elastic sheet with magnetic effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shehzad et al 7 analyzed the Casson liquid stream with radiation effect. The impact of chemical reaction on the stream of Casson liquid through a stretching surface was addressed by Khan et al 8 Nandeppanavar et al 9 scrutinized the radiation effect on convective stream of a Casson liquid instigated by a moving upright plate. Alkasasbeh et al 10 scrutinized the blood‐based Casson nanofluid stream over an elastic sheet with magnetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of magnetic effect on the mixed convective flow past an elastic sheet with a permeable medium was examined by Hayat et al 18 Das et al 19 inspected the convective heat transfer of a viscous liquid stimulated by an impermeable stretching sheet. Nandeppanavar et al 9 scrutinized the radiation effect on the convective stream of a Casson liquid instigated by a moving upright plate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their numerous mechanical uses, such as the assembly of plastic sheets, the execution of greases and the formation of organic liquids, researchers are considering studying the properties of non-Newtonian liquids. The effect of radiative slip on MHD non-Newtonian stream of stretching sheet in presence of porous medium is analyzed by Kumar et al 12 Mahantesh et al 13 demonstrated convective Casson fluid flow heat and mass transfer over a moving vertical plate using nonlinear thermal radiation and convective boundary constraints. Liaquat et al 14 and Liaquat et al 15 investigated the triple solution and stability analysis of Casson fluid stream of MHD stagnation point with thermal radiation and convective effects.…”
Section: Introductionmentioning
confidence: 99%
“…Nandeppanavar et al. 7 deliberated heat and mass transfer of Casson fluid flow subjected to convective boundary conditions and nonlinear thermal radiation on a vertical plate. Sohail et al.…”
Section: Introductionmentioning
confidence: 99%